Cropping geometry and in situ soil moisture conservation practices in upland rice(Oryza sativa L.) - Gunturi Alekhya (Department of Agronomy, College of Agriculture, 2020)
Cropping geometry and in situ soil moisture conservation practices in upland rice (Oryza sativa L.) A field experiment entitled “Cropping geometry and in situ soil moisture conservation practices in upland rice (Oryza sativa L.)” was conducted at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram during Kharif, 2019 with the objectives to study the influence of cropping geometry and in situ soil moisture conservation practices on growth and yield of upland rice and to work out the economics of cultivation. The variety used was Aiswarya (PTB 52). The experiment was laid out in randomized block design with 9 treatments and three replications. The treatments were T1: Normal planting of upland rice (20 cm x 10 cm), T2: Normal planting with live mulching of cowpea, T3: Normal planting with live mulching of cowpea and hydrogel application, T4: Normal planting with live mulching of cowpea and coir pith compost application, T5: Normal planting with live mulching of cowpea and hydrogel + coir pith compost application, T6: Paired row planting with live mulching of cowpea, T7: Paired row planting with live mulching of cowpea and hydrogel application, T8: Paired row planting with live mulching of cowpea and coir pith compost application, T9: Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application.. The results revealed that the treatment T5 (Normal planting with live mulching of cowpea and hydrogel + coir pith compost application) produced taller plants at 60 DAS and the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) produced the tallest plants at harvest and highest number of tillers at 60 DAS. Leaf area index was not significantly influenced by the treatments, though the treatment T9 showed the highest value of LAI at 60 DAS. The maximum dry matter production was recorded in the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) at 60 DAS and harvest. The yield attributes viz., productive tillers m-2, grain weight panicle-1, number of spikelets panicle-1, 1000 grain weight, grain yield, straw yield and harvest index were significantly higher in the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) and the treatment T5 (Normal planting with live mulching of cowpea and hydrogel + coir pith compost application) registered the highest length of panicle and percentage of filled grains panicle-1. The treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) produced the highest grain yield of 3443 kg ha-1 and straw yield of 3737 kg ha-1. The maximum harvest index of 0.48 was recorded in the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application). The nutrient uptake of N, P and K were highest for the treatment T9. The availability of all nutrients (N, P and K) after the experiment were significantly influenced and the treatment T9 showed the highest availability of all the nutrients. The root parameters viz., root shoot ratio, root weight and root volume were not significantly influenced by the treatments, whereas root length was favourably influenced by the treatments and the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) produced the highest root length. The economic analysis revealed that the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application) resulted in the highest net income. The treatment T7 (Paired row planting with live mulching of cowpea and hydrogel application) showed the maximum BC ratio and was on par with the treatment T9. The results revealed that higher growth characters, yield attributes and yield of upland rice was recorded by the treatment T9 (Paired row planting with live mulching of cowpea and hydrogel + coir pith compost application). Maximum net income was also recorded by the treatment T9 and was on par with the treatment T7. Therefore, paired row planting with live mulching of cowpea along with combined application of hydrogel and coir pith compost could be recommended for upland rice.